Mutation Induction using Colchicine in Shallot Bulbs (Allium ascalonicum L.) of Tajuk Variety - Husain, Indriati; Surdaya, Tedy; Purnomo, Sutrisno Hadi (Jurnal Hortikultura Indonesia, 2022)
Techniques in the fold of shallot plant breeding can be done to obtain or improve existing characters to be better than before. One of them is the mutation induction technique with a chemical mutagen, namely colchicine. The purpose of the study was to find out the effect of colchicine concentration on growth, yield, character diversity and obtain value of Lethal Concentration 20-50% (LC20-50) for Tajuk Vriety M1 of shallot. The research was conducted in July-October 2019 in Libuo Village of Dungingi District of Gorontalo City. The study was conducted using a design randomized block design (RBD) with six level of colchicine solution concentration (0, 0.1, 0.2, 0.3, 0.4 and 0.5% (w/v)) with three repeats. The results of the variety analysis showed that a solution of colchicine concentration of 0-0.5% had the effect on the morphology of leaf colour, the number of saplings and the percentage of seeds growing abnormally and character of lear colour shallot varieties of mutant putative generation M1, but had no significantly effect on plant height, number of bulbs, wet and dry weights. CurveExpert1.3 analysis result, the lethal concentration value of colchicine solution in shallot bulbs can be obtained at a concentration of 0.33 (w/v) at LC30. Keywords: abnormal, LC30, LC50, mutagen, putative mutant